Cantaloupe Facilitates Salmonella Typhimurium Survival Within and Transmission Among Adult House Flies (Musca domestica L.) - Thomson, Jessica L; Cernicchiaro, Natalia; Zurek, Ludek; Nayduch, Dana (Foodborne pathogens and disease, 2021)
Salmonella enterica serovar Typhimurium is a pathogen harbored by livestock and shed in their feces, which serves as an acquisition source for adult house flies. This study used a green fluorescent protein (GFP) expressing strain of Salmonella Typhimurium to assess its acquisition by and survival within house flies, and transmission from and between flies in the presence or absence of cantaloupe. Female house flies were exposed to manure inoculated with either sterile phosphate-buffered saline or GFP-Salmonella Typhimurium for 12 h, then used in four experiments each performed over 24 h. Experiment 1 assessed the survival of GFP-Salmonella Typhimurium within inoculated flies. Experiment 2 determined transmission of GFP-Salmonella Typhimurium from inoculated flies to cantaloupe. Experiment 3 assessed fly acquisition of GFP-Salmonella Typhimurium from inoculated cantaloupe. Experiment 4 evaluated transmission of GFP-Salmonella Typhimurium between inoculated flies and uninoculated flies in the presence and absence of cantaloupe. GFP-Salmonella Typhimurium survived in inoculated flies but bacterial abundance decreased between 0 and 6 h without cantaloupe present and between 0 and 6 h and 6 and 24 h with cantaloupe present. Uninoculated flies acquired GFP-Salmonella Typhimurium from inoculated cantaloupe and bacterial abundance increased in cantaloupe and flies from 6 to 24 h. More uninoculated flies exposed to inoculated flies acquired GFP-Salmonella Typhimurium when cantaloupe was present than when absent. We infer that the presence of a shared food source facilitated the transfer of GFP-Salmonella Typhimurium from inoculated to uninoculated flies. Our study demonstrated that house flies acquired, harbored, and excreted viable GFP-Salmonella Typhimurium and transferred bacteria to food and each other. Understanding the dynamics of bacterial acquisition and transmission of bacteria between flies and food helps in assessing the risk flies pose to food safety and human health.
Keywords: house flies; Salmonella enterica; zelené fluorescenční proteiny; Houseflies; Musca domestica; Female; Green Fluorescent Proteins; zvířata; Food Microbiology; food safety; pathogen transmission; vector potential; ženské pohlaví; moucha domácí; Cucumis melo; kontaminace potravin; Food Contamination; Salmonella typhimurium; Animals; potravinářská mikrobiologie